The importance of Leptospira interrogans serovars Icterohaemorrhagiae and Canicola in coastal zone and in southern fields of Rio Grande do Sul, Brazil - Silva, Felipe J. [UNESP]; Santos, Carlos E. P.; Silva, Glaucenyra C. P. [UNESP]; Santos, Renata F. [UNESP]; Curci, Vera C. M.; Mathias, Luis A. [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
This study aimed to describe the occurrence of Leptospira interrogans serovars Icterohaemorrhagiae and Canicola, in coastal zone and in southern grasslands of Rio Grande do Sul, Brazil. In each one of the four analyzed farms blood samples were collected from free-living wild animals, domestic animals and humans to perform serological testing for leptospirosis. The presence of antibodies was verified by microscopic agglutination test (MAT). The criterion adopted to consider a serum as agglutination reactant was at least 50% of leptospira for a microscopic field of 100x. From 17 blood samples collected at Chuí, five (29.41%) were positive, three (60.00%) for serovar Icterohaemorrhagiae and two (40.00%) for Canicola. From 21 samples collected in the County of Santana da Boa Vista, six (28.57%) were positive, four (66.67%) for serovar Canicola and two (33.33%) for serovar Icterohaemorrhagiae. From 32 samples collected at Alegrete, 10 (31.25%) were positive, seven (70.00%) for serovar Icterohaemorrhagiae and three (30.00%) foro serovar Canicola. From 17 blood samples collected in Cruz Alta, three (17.64%) were positive, two (66.67%) for serovar Icterohaemorrhagiae and one (33.33%) for Canicola. It is necessary to improve sanitary practices on farms in the state of Rio Grande do Sul, in order to achieve success in leptospirosis control programs.

O presente estudo teve como objetivo descrever a ocorrência de Leptospira interrogans sorovariedades Icterohaemorrhagiae e Canicola, na zona litorânea e nos campos sulinos do Estado do Rio Grande do Sul. Em cada uma das quatro propriedades foram realizadas colheitas de sangue de animais selvagens de vida livre, de animais domésticos e de seres humanos para realização de sorologia para leptospirose. A presença de anticorpos foi verificada pela técnica de Soroaglutinação Microscópica (SAM). O critério adotado para considerar um soro como reagente foi aglutinação de pelo menos 50% das leptospiras no campo microscópico no aumento de 100x. Das 17 amostras de sangue colhidas na propriedade pertencente ao Município de Chuí, cinco (29,41%) foram positivas, três (60,00%) à sorovariedade Icterohaemorrhagiae e duas (40,00%) à Canicola. Das 21 amostras colhidas em Santana da Boa Vista, seis (28,57%) foram positivas, quatro (66,67%) à Canicola e duas (33,33%) à Icterohaemorrhagiae. Das 32 amostras colhidas em Alegrete, 10 (31,25%) foram positivas, sete (70,00%) à Icterohaemorrhagiae e três (30,00%) à Canicola. Das 17 amostras colhidas em Cruz Alta, três (17,64%) foram positivas, duas (66,67%) à Icterohaemorrhagiae e uma (33,33%) à Canicola. É necessário melhorias nas práticas sanitárias em propriedades rurais do Estado do Rio Grande do Sul, a fim de se obter sucesso em programas locais de controle da leptospirose.
A importância de Leptospira interrogans sorovariedades Icterohaemorrhagiae e Canicola na zona litorânea e nos campos sulinos do Rio Grande do Sul
Keywords: Leptospirose; Leptospira interrogans; propriedades rurais; Estado do Rio Grande do Sul; Leptospirosis; Leptospira interrogans; farms; Rio Grande do Sul